Spirapril – a modern ACE inhibitor - V. M. Gorbunov (Кардиоваскулярная терапия и профилактика, 2005)
An ACE inhibitor, spirapril, is widely used in modern cardiology practice. Its pharmacokinetics is characterized by prolonged elimination half-life, >24 hours. There is no need for dose titration, even in patients with chronic renal failure. The medication is effective in treating individuals with chronic heart failure. Various aspects of spirapril therapy are being studied in Russian-based clinical trials.